Kepemilikan Institusional Memoderasi Thin Capitalization, Capital Intensity, dan Ukuran Perusahaan terhadap Tax Avoidance - Rachmania, Dewi; Zahra, Awalia Az (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine whether Institutional Ownership Moderates Thin Capitalization, Capital Intensity, and Company Size on Tax Avoidance in Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2020-2024. This study uses a quantitative approach. The population in this study includes Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024. The sampling technique uses the Purposive Sampling method. Based on the established criteria, 8 company samples were obtained. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange. The method used in this study is panel data regression analysis. The results of this study indicate that simultaneously Thin Capitalization, Capital Intensity, and Firm Size together have an effect on Tax Avoidance. Partially, Thin Capitalization has no effect on Tax Avoidance, Capital Intensity has a positive effect on Tax Avoidance, Company Size has a positive effect on Tax Avoidance, Institutional Ownership is unable to moderate Thin Capitalization and Firm Size on Tax Avoidance, while Institutional Ownership can strengthen the moderation of Capital Intensity on Tax Avoidance.